Chemical Composition and Antioxidant Activities of Essential Oils from Local Cinnamon (Cinnamomum burmannii) (Minang Chemistry Journal (MCJ), 2026)
The essential oil of Cinnamomum burmannii bark harvested in West Sumatra was extracted by steam distillation and analyzed by GC-MS. Cinnamaldehyde was identified as the major active component (74.2%). The antioxidant activity was measured using the DPPH radical scavenging assay, yielding an IC50 value of 18.5 ug/mL. These results suggest that local cinnamon essential oil has strong potential as a natural food preservative and pharmaceutical ingredient.